Optimalisasi Pemanfaatan Cangkang Kerang untuk Penjernihan Air Rawa Desa Burai Ogan Ilir - Ulfa M Nur; A Ogara; Heru Heru; MDA Mukti; MR Khatami; M Fitrani (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2021)
Nur UM, Ogara A, Heru H, Mukti MDA, Khatami MR, Fitrani M. 2021. Optimizing the utilization of seashells for purification of swamp water in Burai Village of Ogan Ilir District. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-9 Tahun 2021, Palembang 20 Oktober 2021. pp. 289-295. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).One of the natural resources that must be a concern for all parties because it has decreased the availability of clean water. Most regions in Indonesia have adequated water resources in terms of quantity, but inadequate in terms of quality, one of which is swamp waters. This article aimed to review the optimization of the use of clam shells for purifying swamp water in Burai Village, Ogan Ilir. The filtration system used three stages of neutralization, coagulation, and filtration. Clam shell could reduce iron levels because they contained high calcium carbonate (CaCO3). In addition, clam shells also had high chitosan substances so that they could increase the pH value of swamp water such as neutralizing pH, water becomes clear, and odorless, so that it was safe to use for meeting household needs. The use of clam shells in the swamp water filtration process could improve the quality of swamp water, so that swamp water in Burai Village, Ogan Ilir Regency could be used for community household needs which included bathing, washing, and latrine activities. So that people didn't have to worry about the availability of clean water especially when entering the dry season.